2023
DOI: 10.1039/d2ra08021d
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of theoretical studies on electro- and photo-chemical conversion of CO2with single-atom catalysts

Abstract: Recent progress of theoretical studies on electro- and photo- chemical conversion of CO2 with single-atom catalysts has been presented, from the intermediates to the final products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 212 publications
(261 reference statements)
0
6
0
Order By: Relevance
“…5c and d), respectively. In addition, they found that the equimolar ratio of Ir 20 Pd 20 Pt 20 Rh 20 Ru 20 HEA has 2 times the activity of Pt (111), and the activity of Ir 10.2 Pd 32.0 -Pt 9.30 Rh 19.6 Ru 28.9 is 5 times higher than that of Pt (111), on which the overpotential is 0.04 V (Fig. 5e).…”
Section: Theoretical Studymentioning
confidence: 95%
See 1 more Smart Citation
“…5c and d), respectively. In addition, they found that the equimolar ratio of Ir 20 Pd 20 Pt 20 Rh 20 Ru 20 HEA has 2 times the activity of Pt (111), and the activity of Ir 10.2 Pd 32.0 -Pt 9.30 Rh 19.6 Ru 28.9 is 5 times higher than that of Pt (111), on which the overpotential is 0.04 V (Fig. 5e).…”
Section: Theoretical Studymentioning
confidence: 95%
“…The randomly distributed metal elements promote the formation of a large number of active centers on the surface of HEAs, which is conducive to optimizing the adsorption and desorption of intermediates. Compared with the original Cu (111), AuAgPtPdCu HEAs optimize the binding energy of *OCH 3 and *O (Fig. 8i).…”
Section: Co 2 Reduction Reactionmentioning
confidence: 99%
“…[ 84 ] Similarly, the fabrication of practical and stable SACs remains a major challenge due to the tendency of SACs to flow and aggregate under practical reaction conditions. [ 85 ] MOFs are a class of porous crystalline materials that provide the most effective coordination sites for anchoring individual metal atoms, thereby preventing structural changes during catalysis. [ 86 ] Zhang et al Added the coordination unsaturated Co element and confirmed that Co enters the MOF lattice as a single atom by Fourier transform and wavelet transform.…”
Section: Application Of Sacs In Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…45,46 Thermal catalysis usually exhibits high CO 2 reduction efficiency, but it usually requires harsh reaction conditions at high temperatures and pressures, resulting in rising energy costs and safety concerns. 47 Electrocatalysis is carried out under an external electric field, but due to excessive over-the-point position, it is easy to cause catalytic activity and reduced selectivity. 45 In contrast, photocatalysis and photothermal synergistic catalysis can rely on solar energy, which has the advantages of mild operating conditions, low energy consumption, and good availability.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, scientists have explored many methods for CO 2 conversion, including thermocatalysis, electrocatalysis, photocatalysis, and photothermal synergistic catalysis. , Thermal catalysis usually exhibits high CO 2 reduction efficiency, but it usually requires harsh reaction conditions at high temperatures and pressures, resulting in rising energy costs and safety concerns . Electrocatalysis is carried out under an external electric field, but due to excessive over-the-point position, it is easy to cause catalytic activity and reduced selectivity .…”
Section: Introductionmentioning
confidence: 99%